Pendampingan dan Penerapan Teknologi Tepat Guna untuk Peningkatan Produktivitas Usaha Mebel Kota Kupang - Nursalim Nursalim; Agusthinus S. Sampeallo; Abdul Wahid; Nixson J. Meok (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
The macroeconomic growth in East Nusa Tenggara (NTT) has shown changes for the better in var-ious fields. This improving economic growth has also had a positive impact on the retail business sector. This is indicated by the increasing interest of the people of Kupang city towards wooden furniture. However, the increasing public interest in furniture is a challenge for furniture entrepreneurs to be able to meet these needs. UD. Gusti Karya is a micro business unit that produces furniture in the city of Kupang. UD. Gusti Karya has started its activities since 1997, but until now the turnover generated has continued to decline due to the limited functionality of the furniture machines used. This activity is part of the PPPUD Program in partnership with UD. Gusti Karya. This activity aims to provide solutions to problems that are being faced by UD. Gusti Karya, which is a micro business unit that produces furniture in the city of Kupang. The solution given is related to productivity problems, by providing assistance and the application of more modern multi-functional furniture machines. Because according to partners, so far, they still use manual equipment more, so it is necessary to implement machines that have more modern technology than those currently available. The output that was achieved from the implementation of this program was an increase in productivity which resulted in an increase in partner turnover by 78.9% from the previous one.DOI: https://doi.org/10.26905/abdimas.v6i1.4943